v.2 - Venkataiah, C. (ed.); Banerjea,A. (ed.) (New Delhi, 2009)
The Indian tribes are primarily concentrated in 152 districts. The tribes living in the remaining districts constitute an insignificant fraction of the country's total tribal population. An interesting feature to note is that about one-half (52.79%) of the tribal population of the country lives in only 30 districts each having more than 1 per cent share of the tribal population of the country. These districts form an almost contiguous belt in the mid-Indian region and are shared by the states of Madhya Pradesh Chhattisgarh accounting for about one-third of the total number of districts - Gujarat, Jharkhand, Maharashtra, Rajasthan, Orissa, West Bengal and Meghalaya. Of these, Ranchi, Santal Parganas (both in Jharkhand) and Koraput (Orissa) alone account for more than one-tenth of the tribal population of the country. Altogether, these districts along with Singhbhum, Valsad, Surat, Bastar and Mayurbhanj share among themselves a quarter of the country's tribal population. The Punjab, Haryana, Delhi, Chandigarh and Pondicherry are non-tribal States and Union Territories respectively.
Keywords: Scheduled tribes-India